Assessment of periprocedural hemodynamic changes in arteriovenous malformation vessels by endovascular dual-sensor guidewire. Issue 1 (February 2015) - Orlov, Kirill; Panarin, Vyacheslav; Krivoshapkin, Alexey; Kislitsin, Dmitry; Berestov, Vadim; Shayakhmetov, Timur; Gorbatykh, Anton
Endovascular embolization is an important modality in the treatment of brain AVMs. Nowadays staged embolization is the method of choice for the prevention of perioperative hemorrhagic complications. Current theory suggests that simultaneous occlusion of more than 60% of AVM volume induces significant redistribution local blood flow. That, in turn, may lead to hemorrhage due to AVM rupture. Aside from angiographic findings, there is still no method that predicts the degree of safe partial embolization. Intraluminal measurement of flow velocity and pressure in the vicinity of the AVM nidus might allow detecting the changes in local hemodynamics. That can provide a valuable data and shed the light on the origin of vascular catastrophes. Ten patients underwent 12 embolization sessions with intraluminal flow velocity and pressure monitoring. The measurements were performed by dual-sensor guidewire. The "Combomap" (Volcano) system with Combowire microguidewires was chosen for measurements, as there is a documented experience of safe use of said guidewires in the cerebral vasculature. The findings observed during the study matched empirical data as well as the current physiological hypothesis of AVM hemorrhage. In conjunction with DSA runs, intraluminal flow velocity and pressure monitoring has the potential to become a valuable tool in AVM treatment.